Sternum Length and Rib Cage Dimensions Compared with Bodily Proportions in Adults with Cystic Fibrosis - Louis-Philippe Laurin; Vincent Jobin; François Bellemare (Canadian Respiratory Journal)
BACKGROUND: A greater structural expansion of the rib cage in females compared with males has been described in cystic fibrosis (CF) patients; however, conflicting data exist as to whether an elongation of the bony ribs and sternum contributes to this expansion.